Growth and Meat Quality of Prestice Black-Pied and (Landrace × Large White) × Duroc Pigs - Pavel Nevrkla; Eva Václavková; Pavel Horký; Vendula Kamanová; Zdeněk Hadaš; Zuzana Rečková; Ladislav Máchal (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2018)
The objective of the performed experiment was to evaluate growth performance and selected carcass traits and meat quality parameters in pigs of a native Czech breed Prestice Black-Pied pig (PB) and a commercial hybrid (H) used for meat production. The observation included 40 pigs, 20 pigs of the native breed PB and 20 pigs of the hybrid combination. The PB piglets showed higher (P ≤ 0.05) birth weight than the H piglets. The lifetime weight gain was higher (P ≤ 0.01) in the H pigs than in the PB pigs. The results also showed higher (P ≤ 0.01) backfat thickness in the PB breed than in the H pigs. Lean meat content was higher (P ≤ 0.01) in the hybrid pigs than in the PB breed. Higher (P ≤ 0.01) values of intramuscular fat content were found in the PB pigs than in the H pigs. Drip loss value was higher (P ≤ 0.01) in the H pigs by 1.3 % than in the PB pigs. The PB pigs showed more favourable (P ≤ 0.05) values of pH45,24 in comparison with the hybrid pigs.